All-weather thermal regulation coatings - Hippalgaonkar, Kedar (2022)
Thermally responsive coatings can provide huge opportunities for energy savings in buildings when applied to walls, rooftops and windows. Groundbreaking work on radiative cooling has emerged in the last decade. In a recent issue of Science, Junqiao Wu and coworkers as well as Long Yi and coworkers take this one step forward by using Tungsten-doped Vanadium Dioxide to build a thermal regulatory structure. The temperature-responsive structures have been demonstrated to radiatively cool in the summer and trap heat in the winter. Their work sets the stage for all-weather thermal regulation coatings. In this Preview, we discuss the scientific advancement in the context of multi-functional coatings for sustainability.